2021
DOI: 10.3390/ijms222212285
|View full text |Cite
|
Sign up to set email alerts
|

Early Adventitial Activation and Proliferation in a Mouse Model of Arteriovenous Stenosis: Opportunities for Intervention

Abstract: Background: Arteriovenous fistula (AVF) stenosis remains an important cause of AVF maturation failure, for which there are currently no effective therapies. We examined the pattern and phenotype of cellular proliferation at different timepoints in a mouse model characterized by a peri-anastomotic AVF stenosis. Methods: Standard immunohistochemical analyses for cellular proliferation and macrophage infiltration were performed at 2, 7 and 14 d on our validated mouse model of AVF stenosis to study the temporal pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Interestingly, a recent study showed that blockade of CX 3 CR1 signaling leads to reduced venous stenosis and improved AVF patency using a humanized mouse model [31]. In another study using a mouse stenosis model [32], macrophages were found to infiltrate into the outer layer at a fast rate and slowly decline over time and only minimal macrophage infiltration happened in the neointimal later in the AVF stenosis. The findings from these two animal studies on AVF stenosis suggest that after AVF forms, early intervention by inhibiting CX 3 CR1 signaling may prevent stenosis and improve patency.…”
Section: Biological Processes and Molecular Pathways In Avf Maturatio...mentioning
confidence: 99%
“…Interestingly, a recent study showed that blockade of CX 3 CR1 signaling leads to reduced venous stenosis and improved AVF patency using a humanized mouse model [31]. In another study using a mouse stenosis model [32], macrophages were found to infiltrate into the outer layer at a fast rate and slowly decline over time and only minimal macrophage infiltration happened in the neointimal later in the AVF stenosis. The findings from these two animal studies on AVF stenosis suggest that after AVF forms, early intervention by inhibiting CX 3 CR1 signaling may prevent stenosis and improve patency.…”
Section: Biological Processes and Molecular Pathways In Avf Maturatio...mentioning
confidence: 99%
“…These interactions may also affect proliferation processes in the vessel wall. Chan et al [ 21 ] showed in a mouse model of arteriovenous fistula stenosis that both macrophage infiltration and cellular proliferation in the adventitia occur rapidly in the early stages of vascular remodeling. These results may be important for intervention strategies to prevent arteriovenous fistula maturation failure.…”
mentioning
confidence: 99%